"Didn't I just say that?" Comparing parent report and spontaneous speech as indicators of grammatical development. (February 2017) - Jyotishi, Manya; Fein, Deborah A.; Naigles, Letitia R.
Highlights: Seven grammatical items are compared with children's usage in their spontaneous speech on the same day. Parents of MV-ASD children confirmed few of their children's productions of the seven grammatical items, even though the children produced them. Pronouns were the most difficult for parents to catch in all three groups. Past tense verbs were also frequently missed by mothers of HV-ASD children. Abstract : Background: The Vineland Adaptive Behavior Scales use parental report to examine communication and social skills in children with typical and atypical development, and exhibit high reliability when compared against overall direct testing. However, findings are mixed comparing Vineland communication/language scores with experimenter-administered tests of language. Methods: The current study breaks new ground in comparing Vineland reports with direct observation of children's speech by (a) individual items and (b) level of child functioning, focusing on usage of wh-questions, verb tenses, negation, pronouns and noun-verb combinations. Both 'high-verbal' (HV) and 'middle-verbal' (MV) children with ASD are included, as well as a language-matched TD group. Results: The results revealed that parent report on the Vineland varies in accuracy of capturing the production of grammatical items by young children with ASD and TD children. While parents' assessment of their child's production of noun-verb combinations and 'who/why' was highly accurate, children's production of pronouns was under-rated by parents. Additionally, parents of HV children also under-rated their child's production of past regular verbs. Conclusion: Underestimation of these grammatical elements could lead to mistaken conclusions about their development in ASD or in individual children.